2015
DOI: 10.1021/acs.iecr.5b00493
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Emulsion-Templated Macroporous Polymer Micromixers Characterized by the Bourne Reaction

Abstract: High porosity, interconnected macroporous polymers prepared by the polymerization of high internal phase emulsions (polyHIPEs) stabilized by either surfactants or a combination of surfactants and hydrophobized silica particles were used as micromixers for liquids. The polyHIPEs had permeabilities between 30 and 2550 mD. The extent of micromixing was characterized by a system of two competitive parallel reactions (fourth Bourne reaction) carried out within the polyHIPEs. These competitive reactions, an acid−bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…PH membranes were evaluated as separators in lithium-ion batteries and performed similarly to commercial polyolefin-based separators while exhibiting advantageous thermal and dimensional stabilities . The effectiveness of PHs as micromixers was evaluated by using two parallel reactions and demonstrated that the degree of micromixing increased with the reduction in the size of the interconnecting holes …”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…PH membranes were evaluated as separators in lithium-ion batteries and performed similarly to commercial polyolefin-based separators while exhibiting advantageous thermal and dimensional stabilities . The effectiveness of PHs as micromixers was evaluated by using two parallel reactions and demonstrated that the degree of micromixing increased with the reduction in the size of the interconnecting holes …”
Section: Applicationsmentioning
confidence: 99%
“…139 The effectiveness of PHs as micromixers was evaluated by using two parallel reactions and demonstrated that the degree of micromixing increased with the reduction in the size of the interconnecting holes. 290…”
Section: Macromoleculesmentioning
confidence: 99%
“…Ye et al [5] and Liu et al [6] obtained gold (or platinum) nanoparticle-mediated polyHIPEs with an open-cellular structure (which is critical to accessing catalytic sites). The free PEI macrosurfactants in the system possibly played a critical role, because when minor small surfactants are present in a Pickering emulsion system, open-cellular rather than closed-cellular polyHIPE is obtained [50][51][52][53][54][55].…”
Section: Pei Macrosurfactant-aided Metal Nanoparticle-dictated Polyhipementioning
confidence: 99%
“…Compared with the conventional surfactants, solid particle stabilizers could obviously tailor the morphology of polyHIPEs [49, 44, 45], and a small amount of surfactant added to the Pickering HIPEs was beneficial to prepare macroporous polyHIPEs with a well‐defined open‐cell structure [14]. In addition, emulsion‐templated macroporous polymers could be transformed from a closed cellular structure to open cellular by increasing the emulsification energy for normal [46] and inverse [47] systems when the internal phase was less than 74% of the whole volume.…”
Section: Introductionmentioning
confidence: 99%